Islamic Religious Education in the Digital Era: A Multidisciplinary Analysis of Pedagogy, Technology, and Ethics - Fatin Nabilah Abdul Wahid; Helene Knudstad; Md. Sultan Mahmud; Najeeb Yahya; Mowafg Masuwd (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2025)
The rapid expansion of digital technology has significantly transformed Islamic religious education across formal and informal learning contexts. This article explores Islamic Religious Education (IRE) in the digital era through a multidisciplinary lens, integrating pedagogy, educational technology, and ethical studies. It examines how digital tools reshape teaching strategies, learning interactions, and moral development within Islamic education. By analyzing contemporary digital practices, the study highlights both opportunities—such as increased accessibility and learner engagement—and challenges, including ethical concerns and value preservation. The findings emphasize the need for balanced integration between technological innovation and Islamic ethical principles to ensure meaningful and value-oriented learning outcomes